Peningkatan Kapasitas Kader Posyandu dalam Edukasi Stunting dan Gizi Terpadu - Lusianah Lusianah; Nedra Wati Zaly; Jelita Siska Herlina Hinonaung; Yeanneke Liesbeth Tinungki; Bety Semara Lakhsmi; Sri Rahayu; Supriyadi Supriyadi (Universitas Baiturrahim, 2026)
Stunting remains a major public health problem in Indonesia, especially during the first 1,000 days of life. This educational intervention was conducted in Patengan Village, Bandung Regency, to strengthen the capacity of posyandu cadres in providing education on stunting, balanced nutrition, and maternal and child health. The methods applied included situational analysis, preparation of training modules, cadre training through interactive lectures, group discussions, growth monitoring simulations, and participatory observation. Evaluation was carried out using pre-test and post-test, as well as qualitative assessment through observation and interviews. The results showed a significant improvement in cadre knowledge, with the average score increasing from 70 to 83. Participants also demonstrated greater confidence and motivation in delivering health education, and expressed appreciation for visionary materials such as nutrition gardens, local food utilization, family nutrition literacy, and digital monitoring, although these have not yet been fully implemented. In conclusion, cadre education is an effective initial strategy to strengthen community capacity in preventing stunting. Investment in cadre training not only provides short-term benefits in knowledge improvement but also lays the foundation for transforming posyandu into sustainable community empowerment centers.